Assessment on Radioactive Uranium Contamination of Paddy Soil in Uranium Mine at Southeast China by ICP-MS - Liu, Pinghui; Wei, Changshuai; Zhang, Shumei; Zhu, Chuanming; Xie, Shurong (Asian Journal of Chemistry, 2015)
Plasma mass spectrometry was applied to measure the level of radioactive uranium in 151 paddy soil samples collected from a uranium mine in southeast China and the uranium contamination was assessed. The results showed that the average uranium content in the paddy soil in the active mining region was 7.88 and 11.44 times the soil background value of the Jiangxi Province and of China nationwide, respectively and was 14.50 times that of the control zone; the average uranium content in the paddy soil in unworked mine region was 1.93 and 1.33 times the soil background value of the Jiangxi Province and of China nationwide, respectively and was 2.44 times that of control zone. The coefficient of variation of uranium content in the active mining region was as high as 201.18 %, suggesting strong impact of anthropogenic disturbance factors. The uranium level in the paddy soil in the active mining region was 2.63 times that in the unworked mine region, suggesting that mining activity was an important factor contributing to aggravated uranium contamination in the mine area. The levels of uranium contamination of paddy soil samples collected from different regions were active mining region > unworked mine region > control zone; there was severe or moderate uranium contamination in the active mining region, mild or no uranium contamination in the unworked mine region and no uranium contamination in the control zone.